PENGARUH PENAMBAHAN ION Ca2+ PADA PENGOLAHAN AIR GAMBUT MENGGUNAKAN KOAGULAN KITOSAN (THE EFFECT OF ADDITIONAL Ca2+ IONS ON PEAT WATER TREATMENT USING CHITOSAN COAGULANT) - Putri, Tassya Amalia; Anis, Anis Shofiyani; Titin, Titin Anita Zaharah (Indonesian Journal of Pure and Applied Chemistry, 2024)
Peat water generally has a brownish-red color and organic matter that can pollute the environment so it is not suitable for use. This study aims to determine the effectiveness of chitosan with the addition of salts containing Ca2+ ions, namely CaCO3 and CaCl2, on reducing peat water parameters. The work procedure includes the preparation of chitosan gel and the preparation of CaCO3 and CaCl2 solutions made with concentration variations of 100, 200, 300, 400, and 500 ppm. Determination of organic substance concentration was carried out by permanganometric titration method The effectiveness of increasing pH in the presence of CaCO3 and CaCl2 salts in peat water was 7. The highest turbidity reduction efficiency after coagulation in peat water was 41.98% with the addition of CaCO3 and 37.37%, with the addition of CaCl2 occurred at a concentration of 300 ppm. The highest efficiency of color reduction after coagulation of peat water was with the addition of 60.7% CaCO3, while with the addition of CaCl2 58% occurred with the addition of 200 ppm CaCl2. The efficiency of reducing organic matter in peat water after coagulation with the addition of CaCO3 was 48.35% at a concentration of 300 ppm while with the addition of CaCl2 it was 48.35%. The addition of Ca2+ ions from CaCO3 and CaCl2 salts is considered to increase the effectiveness of chitosan as a coagulant for treating peat water.